Influence of Bile Acids in Hydrogel Pharmaceutical Formulations on Dissolution Rate and Permeation of Clindamycin Hydrochloride - Nebojša Pavlović; Isidora Anastasija Bogićević; Dragana Zaklan; Maja Đanić; Svetlana Goločorbin-Kon; Hani Al-Salami; Momir Mikov (Gels, 2022)
Clindamycin hydrochloride is a widely used antibiotic for topical use, but its main disadvantage is poor skin penetration. Therefore, new approaches in the development of clindamycin topical formulations are of great importance. We aimed to investigate the effects of the type of gelling agent (carbomer and sodium carmellose), and the type and concentration of bile acids as penetration enhancers (0.1% and 0.5% of cholic and deoxycholic acid), on clindamycin release rate and permeation in a cellulose membrane in vitro model. Eight clindamycin hydrogel formulations were prepared using a 23 full factorial design, and they were evaluated for physical appearance, pH, drug content, drug release, and permeability parameters. Although formulations with carbomer as the gelling agent exerted optimal sensory properties, carmellose sodium hydrogels had significantly higher release rates and permeation of clindamycin hydrochloride. The bile acid enhancement factors were higher in carbomer gels, and cholic acid exerted more pronounced permeation-enhancing effects. Since the differences in the permeation parameters of hydrogels containing cholic acid in different concentrations were insignificant, its addition in a lower concentration is more favorable. The hydrogel containing carmellose sodium as a gelling agent and 0.1% cholic acid as a penetration enhancer can be considered as the formulation of choice.